OPTIMISME KESEMBUHAN PADA PENDERITA MIOMA UTERI - Cahyasari, A.M. Setyana Mega; Sakti, Hastaning (Faculty of Psychology, Diponegoro University, 2014)
Abstract Uterine myoma (or uterine fibroid) is the most common tumour in female reproductive structure. It can bringphysical impact, such as pain, abdominal discomfort, and abnormal bleeding. T oÂ cope with uterine myoma, optimism is needed to improve the psychological wel l -being of the affected women. Optimism was defined as apositive attitude i n whi ch person can achieve the expected normal health condition after suffering from uterinemyoma. This study aims to describe the optimism of women diagnosed with a uterine myoma. This qualitativestudy used a phenomenological me t h o d . Two women diagnosed with uterine myoma participated in this study.Interview and observation were used to collect data. The findings showed that women affected uterine myomahad optimism and pessimism fluctuated. Optimism happened after they experienced particular events thatchanged their perscpective. Optimism empowered subjects to cope with uterine myoma. Factors that influencetheir optimism were social support received from family and others, sharing similar experience from otheraffected women, and religiosity. Optimism was also shown through their coping strategies in dealing with uterinemyoma: seeking information, following treatment, applying nutrition diet, and maintaining health status.